2023
DOI: 10.3390/ijms24076535
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of a Combined Bacteriophage–Probiotic Sanitation System to Control Microbial Contamination and AMR in Healthcare Settings: A Pre-Post Intervention Study

Abstract: Microbial contamination in the hospital environment is a major concern for public health, since it significantly contributes to the onset of healthcare-associated infections (HAIs), which are further complicated by the alarming level of antimicrobial resistance (AMR) of HAI-associated pathogens. Chemical disinfection to control bioburden has a temporary effect and can favor the selection of resistant pathogens, as observed during the COVID-19 pandemic. Instead, probiotic-based sanitation (probiotic cleaning hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Yet, in the past decade, there have been fewer than twenty published peer-reviewed studies investigating the efficacy of PBS in practice (Table 1). Many of these in situ studies were conducted in European hospitals and healthcare settings and used the patented Bacillus-based probiotic cleaning and hygiene system developed by Copma (Ferrara, Italy) [8,69,[71][72][73][74][75][76][77]. All studies identified in Table 1 compared the effectiveness of PBS to conventional chemical disinfectants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, in the past decade, there have been fewer than twenty published peer-reviewed studies investigating the efficacy of PBS in practice (Table 1). Many of these in situ studies were conducted in European hospitals and healthcare settings and used the patented Bacillus-based probiotic cleaning and hygiene system developed by Copma (Ferrara, Italy) [8,69,[71][72][73][74][75][76][77]. All studies identified in Table 1 compared the effectiveness of PBS to conventional chemical disinfectants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the stable reduction in the pathogen burden and associated HAIs, switching from chemical disinfectants to PBS eliminated 50-99.9% of the previously identified resistant bacterial strains on hospital surfaces [74,76]. Abatement of resistant staphylococci strains and other multi-drug resistance bacteria was even more successful when lytic bacteriophages was added to the Bacillus-based probiotic cleaning solution [76,80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger follow-up study at two hospitals using the combined PCHS+Phage treatment had mixed results. One hospital showed a significant reduction in Staphylococcus , but the other did not [ 24 ]. This study was performed during the COVID-19 pandemic, which led to the use of emergency applications of 3% NaClO disinfectant.…”
Section: Techniques For Investigating the Microbiome Of The Built Env...mentioning
confidence: 99%
“…This study was performed during the COVID-19 pandemic, which led to the use of emergency applications of 3% NaClO disinfectant. One hospital used a greater number of NaClO applications, and this increase was correlated with an order of magnitude reduction in Bacillus and phage abundance, likely leading to a reduction in the effectiveness of the probiotic intervention [ 24 ]. These results support an earlier study, also performed during the COVID-19 pandemic, that found a reduction in pathogen load through the use of PCHS was reversed when emergency 5% NaClO was implemented [ 91 ].…”
Section: Techniques For Investigating the Microbiome Of The Built Env...mentioning
confidence: 99%